2018
DOI: 10.1186/s12885-018-4855-y
|View full text |Cite
|
Sign up to set email alerts
|

Health utility scores of family caregivers for leukemia patients measured by EQ-5D-3L: a cross-sectional survey in China

Abstract: BackgroundThis study assessed the health related quality of life of family caregivers (FCs) of leukemia patients by using the health utility scores derived from the EuroQol five-dimensional (EQ-5D) questionnaire.MethodsA cross-sectional survey was undertaken on 306 family caregivers of leukemia patients to assess their health utility using the EQ-5D-3L. Participants were recruited from three hospitals in China’s Heilongjiang province. The health utility scores of the participants were estimated based on the Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…Health is a complex concept, so there are many methods and indicators to measure the health status of residents. The European five-dimensional health scale (EQ-5D) is widely used by researchers due to its simplicity and high credibility [23][24][25]. Zhang divided the health of the elderly into three aspects: physical health, cognitive function, and self-evaluated health [26].…”
Section: Outcome Variablesmentioning
confidence: 99%
“…Health is a complex concept, so there are many methods and indicators to measure the health status of residents. The European five-dimensional health scale (EQ-5D) is widely used by researchers due to its simplicity and high credibility [23][24][25]. Zhang divided the health of the elderly into three aspects: physical health, cognitive function, and self-evaluated health [26].…”
Section: Outcome Variablesmentioning
confidence: 99%
“…The initial screening retrieved 9426 citations, and following the data-extraction process, 12 primary studies (reported in 17 publications) were included in the HRQoL burden review (Figure 1). The 12 studies differed in terms of design, study populations, and the instruments used to measure HRQoL burden (Table 1) [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] . The majority of studies were conducted in the United States (n ¼ 6) and Europe (n ¼ 3); study populations included both treated and untreated patients, as well as those with R/R disease.…”
Section: Hrqol Burden Of Cllmentioning
confidence: 99%
“…The quality of life (QoL) was assessed by using the Chinese version EuroQol (EQ-5D-3L)(10), which has been previously validated (11)(12)(13). The questionnaire of EQ-5D-3L consists of two parts.…”
Section: Measures Of Quality Of Life and In Uencing Factorsmentioning
confidence: 99%